2016
DOI: 10.22324/ijhrdppr.1.117
|View full text |Cite
|
Sign up to set email alerts
|

67 The Impact of the Economic Crisis upon Human Resource Development (HRD): Evidence from two Greek Banks

Abstract: This study investigates the nature and changes of Human Resource Development (HRD) in two Greek banks under the challenging context of the economic crisis. It examines the latter's impact upon HRD as it was perceived from different stakeholders and through a pre and ongoing-crisis assessment approach.The study draws upon qualitative research data from two case study banking organizations in Greece, reporting on 76 semi-structured interviews with key stakeholders (HR staff, Bank Managers, employees) undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…The aftermath of the economic crisis affected most banking organizations across the globe, with major restructuring taking place and their HR practices dramatically altered (Mitsakis, ). A recent study from Mitsakis and Aravopoulou () raised concerns about the extent to which strategic HRD (SHRD) is present within organizations under such unfavourable conditions. The authors reported an HRD setback due to the crisis by highlighting its aspirational role within organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The aftermath of the economic crisis affected most banking organizations across the globe, with major restructuring taking place and their HR practices dramatically altered (Mitsakis, ). A recent study from Mitsakis and Aravopoulou () raised concerns about the extent to which strategic HRD (SHRD) is present within organizations under such unfavourable conditions. The authors reported an HRD setback due to the crisis by highlighting its aspirational role within organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Advocates for a human capital approach to developing employees have long espoused the view that investment in employee competencies is required to meet an organization’s strategic goals (Gaudet et al, 2017; Hooi, 2019; Sheehan & Shanahan, 2017). Such approaches identify value in leveraging human assets to enhance productivity and performance, thus increasing competitiveness and sustainability (Mitsakis & Aravopoulou, 2016). In these terms, employees are viewed for their utilitarian value as bundles of knowledge, skills and attributes that are subject to appreciation and depreciation and can be treated as simply another factor in the production process (Nafukho et al, 2004).…”
Section: Human Capital and Hrd: Developing Humans Or Developing Resoumentioning
confidence: 99%
“…11-12). Mitsakis and Aravopoulou (2016) researched approaches to personnel management in the conditions of crisis; crisis management principles of personnel are formulated taking into account the behavioural characteristics of employees (pp. 70-80), while Uitdewilligen and Waller (2018) substantiated the organizational and methodical approach to the formation of professional multidisciplinary teams on Pobrane z czasopisma Annales H -Oeconomia http://oeconomia.annales.umcs.pl Data: 06/10/2020 15:29:59 U M C S crisis management (pp.…”
Section: Review Of Literature On Crisis Managementmentioning
confidence: 99%